Socio-ecological drivers of vulnerabilities of children living within orphan homes and the implications for their nurturance care - Onayemi, Olayinka M.; Hapunda, Given (Frontiers in Public Health, 2023)
At the heart of the Sustainable Development Goals (SDG) is the vision to “leave no one behind, and to see that all children survive, thrive and transform. However, some categories of children may remain left behind owing to their disproportionate exposure to the risk of threats and deficit of attention to the social and ecological climate that characterizes the various systems in which they are found. This study is concerned with one major question: Despite diverse local and international instruments that favor full nurturance and development of children, what social forces play as threat to full nurturance care in the context of children living in Orphan homes? Nurturing care framework and Brofenbrener’s ecological system theory were adopted as the analytical frameworks. Research design was exploratory. Data were collected through sessions of in-depth-interview with orphanage managers, caregivers, and social workers on the socio-ecology drivers of threat to children living within the orphan home space and its implications for nurturance care across the various complex systems of the child’s environment. The study found various factors across the complex systems of child development – microsystem, mesosystem, exosystem, microsysm and lastly, chronosystem- which undermine caregivers’ delivery and increases children’s vulnerability and risk of missing out on effective nurturance care. These vulnerabilities are endemic realities of social, and bio-ecologcal space in which child development occurs. This study recommends specialized interventions and policy directives relevant for each identified threat. It also calls for a stronger political will in improving the conditions of this category of the children while within the orphan home space and ultimately, actions towards deinstitutionalization of children.